Penerapan Pasal 2 Ayat (2) Undang-Undang Nomor 20 Tahun 2001 Tentang Pemberantasan Tindak Pidana Korupsi (Studi Putusan: 29/Pid.Sus-Tpk/2021/PN.Jkt.Pst) - Muniifah, Nur; Isnaini, Isnaini; Kartika, Arie (Universitas Medan Area, 2024)
This study aims to determine the application of Article 2 Paragraph (2) to decision No: 29/Pid.Sus-TPK/2021/PN.Jkt.Pst. The subject matter focuses on how the application of Article 2 Paragraph (2) and the judge's consideration of the decision. The research method used is juridical-normative with a statutory and case approach with data analyzed descriptively and analytically. The results showed that the judge did not apply Article 2 Paragraph (2) but instead applied Article 12 letter b, even though the Covid-19 pandemic was included in the elements of certain circumstances. Whereas judges have the authority to make decisions outside the indictment to create decisions that are in favor of the community. Not applying Article 2 Paragraph (2), the judge could not apply Perma No. 1 of 2020 Sentencing Guidelines Article 2 and Article 3 in his considerations even though the defendant's actions had fulfilled the classification of the Perma. In addition, the mitigating consideration by the judge that the defendant had been found guilty and was reviled by the community did not reflect a just decision with an orientation towards moral, social, and legal justice.